Low temperature characteristic of ITO/SiOx/c-Si heterojunction solar cell. (5th August 2015) - Du, H W; Yang, J; Li, Y; Gao, M; Chen, S M; Yu, Z S; Xu, F; Ma, Z Q
Abstract: Based on the temperature-dependent measurements and the numerical calculation, the temperature response of the photovoltaic parameters for a ITO/SiO x /c-Si heterojunction solar cell have been investigated in the ascending sorting of 10–300 K. Under unique energy concentrated photon irradiation with the wavelength of 405 nm and power density of 667 mW cm −2, it was found that the short-circuit current ( I SC ) was nonlinearly increased and the open-circuit voltage ( V OC ) decreased with temperature. The good passivation of the ITO/c-Si interface by a concomitant SiO x buffer layer leads to the rare recombination of carriers in the intermediate region. The inversion layer model indicated that the band gap of c-silicon was narrowed and the Fermi level of n -type silicon ( ) tended to that of the intrinsic Fermi level ( ) (in the middle of band gap) with the increase of the temperature, which lessened the built-in voltage ( V D ) and thus the V OC . However, the reduction by 90% of V OC is attributed to the shift of in c-silicon rather than the energy band narrowing. Through the analysis of the current–voltage relationship and the data fitting, we infer that the series resistance ( R s ) is not responsible for the increase of I SC, but the absorption coefficient and the depletion-width of c-silicon are the causes of the enhancing I SC . Mostly, the interaction of the photon-generated excess 'cold hole' and the acoustic phonon in n-Si would influence the variation of I ph or I SC with temperature.